Módulo IP de um Demultiplexador para o Subsistema Fluxo de Transporte- MPEG-2-Aderente ao Sistema Brasileiro de TV Digital - Medeiros, Leonardo (2010)
In the Brazilian scenario, the development of hardware components through computational methodologies and tools, available at affordable costs to education and research centers have make it feasible to design blocks and integrated circuit modules up to intellectual property IP level, focusing strategic areas of industry, specially those dedicated to the components for the Brazilian Digital Television System (SBTVD). This work deals with the architectural proposal development and validation for the Transport Stream MPEG-2 TS Subsystem of SBTVD transport stream demultiplexer from its specification and high-level modeling to its technology mapping implementation. As specific results, the structural and functional requirements of Transport Stream Subsystem MPEG-2 TS are detailed, the development of a software model for the demultiplexer and of an environment containing MPEG-2 TS flows that can validate the compliance with the SBTVD specification of models, an RTL-level MPEG-2 TS demultiplexer IP conceptual proof implementation and validation and its prototyping with technology mapping for FPGA and an ASIC design kit , are also presented.